Creating a protocol for collaborative mobile applications for kids between 4 and 6 years old - Ramírez Benavides, Kryscia Daviana (2015)
One of the basic requirements in education is to prepare students for participation in an information society in which knowledge will be the most important resource for development. Computer-Supported Collaborative Learning is one of the most promising approaches to enhance the learning process with the help of information and communication technology. At the same time, advances in technology and mobile devices in the last decade have increased the number of educational institutions adopting mobile tools in the learning process. This paper describes the design and implementation of a protocol for a collaborative mobile application. TITIBOTS Colab is a programming environment for kids between 4 and 6 years old. During the implementation of TITIBOTS Colab, while creating a working version of the protocol, our team found that all messages defined in the design worked properly in order to provide the communication rules for the client and server applications.